2019
DOI: 10.1161/circresaha.118.313650
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapy for Heart Failure Associated With Pulmonary Hypertension

Abstract: The past 2 decades have witnessed a >40% improvement in mortality for patients with heart failure and left ventricular systolic dysfunction. 1 This success has coincided with the stepwise availability of drugs that target neurohormonal activation: β-adrenergic receptor blockers (β-blockers), ACE (angiotensin-converting enzyme) inhibitors and ANG (angiotensin) II blockers, neprilysin inhibitors, and aldosterone antagonists. Our understanding of right heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 137 publications
3
40
0
Order By: Relevance
“…Systolic function of the right ventricle is sensitive to changes in afterload, and small increases in pulmonary artery pressure can result in large reductions in stroke volume (SV). Therefore, reducing afterload of the right ventricle is the cornerstone of prevention and management of RVF due to pulmonary hypertension 9 . In our study, RHF occurred in both cases without iNO treatment, while not the three cases with iNO treatment, indicating that iNO treatment might reduce the risk of developing RHF in COVID‐19 patients as previously reported for the treatment of fat embolization syndrome 10 …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Systolic function of the right ventricle is sensitive to changes in afterload, and small increases in pulmonary artery pressure can result in large reductions in stroke volume (SV). Therefore, reducing afterload of the right ventricle is the cornerstone of prevention and management of RVF due to pulmonary hypertension 9 . In our study, RHF occurred in both cases without iNO treatment, while not the three cases with iNO treatment, indicating that iNO treatment might reduce the risk of developing RHF in COVID‐19 patients as previously reported for the treatment of fat embolization syndrome 10 …”
Section: Discussionsupporting
confidence: 80%
“…Therefore, reducing afterload of the right ventricle is the cornerstone of prevention and management of RVF due to pulmonary hypertension. 9 In our study, RHF occurred in both cases without iNO treatment, while not the three cases with iNO treatment, indicating that iNO treatment might reduce the risk of developing RHF in COVID-19 patients as previously reported for the treatment of fat embolization syndrome. 10 Based on our study, we found that treatment with iNO was beneficial in reducing and stabilizing the PASP in the critically ill COVID-19 patients with pulmonary hypertension, especially in the early stage of pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“… 69–71 PH, defined by a mean pulmonary artery pressure (mPAP) ≥25 mm Hg at rest, is the most common cause of Right Heart Failure (RHF). 72 In patients with severe COVID-19, multiple concomitant mechanisms seem to contribute to the development of PH, this including cytokine storm, endothelial injury, hypercoagulability attributing to development of venous thromboembolism, worsening myocardial injury, and the presence of thrombotic microangiopathy. 70 …”
Section: Discussionmentioning
confidence: 99%
“…PH-LHD is defined as a mean pulmonary artery pressure of > 20 mmHg with a concomitant pulmonary artery wedge pressure of > 15 mmHg (7). As we uncover more about PH-LHD, it is becoming increasingly apparent that the pathophysiologic aberrations and the phenotypic variations are highly dependent on the underlying cardiovascular disease process, e.g., heart failure with reduced ejection fraction (HFrEF) vs. heart failure with preserved ejection fraction (HFpEF) (4, 7,8).…”
mentioning
confidence: 99%